SIRT2 plays complex roles in neuroinflammation neuroimmunology-associated disorders - Lu, Wenmei; Ji, Haonan; Wu, Danhong (Frontiers in Immunology, 2023)
Neuroinflammation and neuroimmunology-associated disorders，including ischemic stroke and neurodegenerative disease, commonly cause severe neurologic function deficits, including bradypragia, hemiplegia, aphasia, and cognitive impairment, and the pathological mechanism is not completely clear. SIRT2, an NAD+-dependent deacetylase predominantly localized in the cytoplasm, was proven to play an important and paradoxical role in regulating ischemic stroke and neurodegenerative disease. This review summarizes the comprehensive mechanism of the crucial pathological functions of SIRT2 in apoptosis, necroptosis, autophagy, neuroinflammation, and immune response. Elaborating on the mechanism by which SIRT2 participates in neuroinflammation and neuroimmunology-associated disorders is beneficial to discover novel effective drugs for diseases, varying from vascular disorders to neurodegenerative diseases.